(untitled) (Revista Sistemas de Producción Agroecológicos, 2015)
A review on the macroeconomic aspects of agriculture and agricultural policy in Colombia took place, and that livestock production is developed around populations of cattle, pigs, goats, poultry, sheep, buffaloes and horses, bovine them is the more representative in terms of the number of individuals, surpassed only by birds, where 57% of bovine meat production is 4% to 39% milk and dual purpose. Furthermore, it has been shown that the livestock sector in Colombia is especially important in the face of climate change mitigation mainly because 44.9% of emissions of greenhouse gases (GHGs) in the country came from agriculture, and 8.9 % occurred due to changes in land use, and both values ​​have grown by over 10% in recent years. It is shown that small farmers play a predominant role in Colombian agriculture, since households in the rural economy constitute 12% of households in Colombia, representing the majority of households in the agricultural sector and make up 90% of the agricultural labor, harvest half the area sown to crops, and have substantial portions of livestock. In this context the government intervenes in the agricultural sector through credit policies, pricing, and trade as export subsidies and restrictions on imports and exports, resulting in promotion of development of productive projects in the field, which encourages job creation and increased income in rural areas.